Tiskane in elektronske oblike znanstvenih in strokovnih serijskih publikacij s področja tehnike v Sloveniji in upoštevanje standardov za njihovo oblikovanje - Jamar, Nina (Knjižnica, 2006)
The importance of standards that determine the layout of serials and contributions is increasing. In the case of the printed format of serials the importance of standardization is also acknowledged by the Ministry of Higher Education, Science and Technology. Adherence to ISO standards for documentation is required for the financial support of this ministry. Standardization of the emerging electronic formats of serials is still in progress. There are guidelines, but there are no standards that would determine the necessary layout, content and the data. Users of these publications need the essential information to determine the relevance of the document. For all the reasons mentioned above, the adherence to standards and other recommendations for the printed and electronic formats for some of scientific and scientific serials from the technical field published in Slovenia was analysed. The sample of seven serials revealed that the most obvious weaknesses are untimely appearance and absence of ISSN of electronic formats. The results could contribute to a better quality of serial publications in Slovenia.
Keywords: serijske publikacije; znanstvene publikacije; strokovne publikacije; standardi; tehnika